Meningkatkan Ekonomi Kreatif Melalui Olahan Tumis Cumi-Cumi - Nurul Hidayat; Abi Dermawan; Firdasari Indamala; Irfan Selutan; Jumi Maria; Marcella Risa; Muhammad Aldo; Siti Nadiah; Windi Siong (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service activity aims to increase the potential of the creative economy through the processing of marine products, especially squid, into a culinary product with selling value, namely sauteed balado squid. This activity was held in Kampung Satu Village, Central Tarakan District, Tarakan City, North Kalimantan Province, on Tuesday, May 6, 2025, at 09.00–15.00 WITA, at the Kramik Boarding House of Mr. Nurul, Jl. Pulau Banda, Kampung Satu Skip. This activity aims to provide training to the community in processing squid into ready-to-sell processing, as well as opening up local culinary business opportunities. The methods used include community service approaches, direct training, and activity documentation. The results of the activity showed an increase in the participants' skills in processing squid into products of economic value and an increase in public interest in entrepreneurship in the culinary sector. With this activity, it is hoped that the community will be able to create superior processed products based on local potential that are able to compete in the digital market, thereby encouraging the growth of the creative economy in coastal communities